Answer:
H
Step-by-step explanation:
given y = -x² + 3x.
let f(x) be y.
f(-2) = -(-2)² + 3(-2) = -10
f(-1) = -(-1)² + 3(-1) = -4
f(0) = -(0)² + 3(0) = 0
f(1) = -(1)² + 3(1) = 2
f(2) = -(2)² + 3(2) = 2
Hiya. I'm going to rewrite the second equation.
By subtracting 5x by both sides, I'll be able to have y by itself:
-y=-5x+13
I'm going to then divide both sides by -1 to get:
y=5x-13.
Then, I'm going to plug that equation into the first equation
3x+2(5x-13)=39
Factor:
3x+10x-26=39
Combine like terms:
13x=65
Divide both sides by 13 to get x by itself to get x=5
Plug this back into the equation of y=5x-13
y=5(5)-13 to get y=12
Answer:
d
Step-by-step explanation:
Soooo,
d = 2r
(29) = 2r
29/2 = 2r/2
14.5 = r